Registries for Biliary Atresia and Related Disorders - Petersen, Claus; Madadi-Sanjani, Omid (European Journal of Pediatric Surgery, 2015)
Most neonatal cholestatic disorders are rare diseases (RD), but they represent the leading indication for pediatric liver transplantation. From the pediatric surgical point of view, biliary atresia (BA) and choledochal cyst are from particular interest because diagnostic pathways and therapeutic algorithms are diverging as well as outcome parameters of follow-up studies. In addition, screening programs for BA are still at an early stage while transition of those patients with and without liver transplantation is not established yet. The newly created Web site www.bard-online.com focuses on BA and related diseases and includes decentralized online registries, information for patients and health workers, as well as a platform for interdisciplinary communication and service offerings. This initiative was started to compensate for disadvantages for patients with RD and to help unifying the community of clinicians and researchers in this field.
Keywords: biliary atresia; neonatal cholestasis; registries; choledochal cyst